2022
DOI: 10.1097/moo.0000000000000799
|View full text |Cite
|
Sign up to set email alerts
|

Review of the effect of amylase-resistant dysphagia products on swallowing safety

Abstract: Purpose of reviewThickened fluids are a widely utilised compensatory management strategy for people with impaired swallowing (dysphagia). Over recent years there has been a shift in practice to offer gum-based instead of starch-based products. A key marketing message has been that gum-based thickeners with amylase-resistant properties are superior in promoting 'safer swallowing'. This review sought evidence to evaluate the effect of amylase-resistant products on swallowing safety. Recent findingsNo studies dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Cichero [ 56 ] and Burning [ 57 ] highlighted a shift from starch-based dysphagia products to gum-based ones, citing improved palatability, stable thickness, and patient preference for serving temperature. Leonard et al conducted a clinical trial with 118 enrolled dysphagia patients, comparing gum-thickened matrices to thin water and starch-thickened ones, all designated as having the consistency of nectar [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cichero [ 56 ] and Burning [ 57 ] highlighted a shift from starch-based dysphagia products to gum-based ones, citing improved palatability, stable thickness, and patient preference for serving temperature. Leonard et al conducted a clinical trial with 118 enrolled dysphagia patients, comparing gum-thickened matrices to thin water and starch-thickened ones, all designated as having the consistency of nectar [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study on 120 post-stroke patients with dysphagia showed that gum-based thickeners with a viscosity range of 150 to 800 mPa.s significantly improved swallowing safety [ 59 ]. Burnip [ 57 ] and Cichero [ 56 ] noted that applying these recommendations clinically may be limited due to the viscosity labeling system’s requirement of laboratory-grade rheometers and engineering expertise.…”
Section: Resultsmentioning
confidence: 99%
“…Thickeners are made from either starch or gum. The present study focuses on gum‐based thickeners only, which are preferable for dysphagia management, offering better palatability and improved stability of thickness over time and different temperatures 21–25 . In addition, experimental investigations with different types of thickener have confirmed the perception of gum‐based liquids being ‘slippery’ compared to other types of thick liquid, making them a suitable option for successful swallowing 19 …”
Section: Introductionmentioning
confidence: 91%